Melanocortin 1 receptor-signaling deficiency results in an articular cartilage phenotype and accelerates pathogenesis of surgically induced murine osteoarthritis. - Julia Lorenz (Public Library of Science (PLoS), 2014)
Proopiomelanocortin-derived peptides exert pleiotropic effects via binding to melanocortin receptors (MCR). MCR-subtypes have been detected in cartilage and bone and mediate an increasing number of effects in diathrodial joints. This study aims to determine the role of MC1-receptors (MC1) in joint physiology and pathogenesis of osteoarthritis (OA) using MC1-signaling deficient mice (Mc1re/e). OA was surgically induced in Mc1re/e and wild-type (WT) mice by transection of the medial meniscotibial ligament. Histomorphometry of Safranin O stained articular cartilage was performed with non-operated controls (11 weeks and 6 months) and 4/8 weeks past surgery. µCT-analysis for assessing epiphyseal bone architecture was performed as a longitudinal study at 4/8 weeks after OA-induction. Collagen II, ICAM-1 and MC1 expression was analysed by immunohistochemistry. Mc1re/e mice display less Safranin O and collagen II stained articular cartilage area compared to WT prior to OA-induction without signs of spontaneous cartilage surface erosion. This MC1-signaling deficiency related cartilage phenotype persisted in 6 month animals. At 4/8 weeks after OA-induction cartilage erosions were increased in Mc1re/e knees paralleled by weaker collagen II staining. Prior to OA-induction, Mc1re/e mice do not differ from WT with respect to bone parameters. During OA, Mc1re/e mice developed more osteophytes and had higher epiphyseal bone density and mass. Trabecular thickness was increased while concomitantly trabecular separation was decreased in Mc1re/e mice. Numbers of ICAM-positive chondrocytes were equal in non-operated 11 weeks Mc1re/e and WT whereas number of positive chondrocytes decreased during OA-progression. Unchallenged Mc1re/e mice display smaller articular cartilage covered area without OA-related surface erosions indicating that MC1-signaling is critical for proper cartilage matrix integrity and formation. When challenged with OA, Mc1re/e mice develop a more severe OA-pathology. Our data suggest that MC1-signaling protects against cartilage degradation and subchondral bone sclerosis in OA indicating a beneficial role of the POMC system in joint pathophysiology.